Pengembangan m-LKPD berbasis proyek berbantuan smart apps creator 3 untuk menstimulus keterampilan proses sains - Kurniawan Saputra; Kartini Herlina; Feriansyah Sesunan (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2021)
This research intends to develop m-LKPD (mobile lembar kerja peserta didik) based on a project assisted by smart apps creator 3 in the diffraction of light lesson validly and practically. m-LKPD develops to stimulate scientific processes skill as multimedia to support online learning in this Covid-19 pandemic. This research uses Design and Development Research (DDR), consisting of 4 stages: analysis, design, development, and evaluation. The instruments used in this research are interview guidelines, validation test questionnaire, practicality test questionnaire, teacher perception questionnaire, student response questionnaire, and assessment rubrics of scientific processes skill. The result of the validation test results 3,62, with a very valid category. The outcome of the practicality test is 90% as a percentage average, with a very practical as a category. The result of stimulating scientific processes skills through a small team test gets 88% as an average percentage with stimulated as a category. This shows that m-LKPD develops very valid and efficient ways to stimulate processes skills. Besides, m-LKPD creates the potential to be implemented in online learning and face-to-face learning, proven by students’ responses gaining 94% with very good as a category and teachers’ perceptions that achieve 96% average percentage with very good as a category. Therefore, the developed m-LKPD can be used as multimedia to support online learning in this Covid-19 pandemic.